2012
DOI: 10.1016/j.stem.2012.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Human ES- and iPS-Derived Myogenic Progenitors Restore DYSTROPHIN and Improve Contractility upon Transplantation in Dystrophic Mice

Abstract: SUMMARY A major obstacle in the application of cell-based therapies for the treatment of neuromuscular disorders is obtaining the appropriate number of stem/progenitor cells to produce effective engraftment. The use of embryonic stem (ES) or induced pluripotent stem (iPS) cells could overcome this hurdle. However to date, derivation of engraftable skeletal muscle precursors that can restore muscle function from human pluripotent cells has not been achieved. Here we applied conditional expression of Pax7 in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
486
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(510 citation statements)
references
References 44 publications
5
486
1
1
Order By: Relevance
“…Although significant progress has been made in terms of improving the efficiency of iPS cell generation through the use of chemical compounds [46,47] and different cell types [48,49], interfering with the epigenetic status of donor cells [50][51][52], or modulating different signal pathways [34,53,54], the quality of iPS cells to date is not significantly improved or even getting worse when the p53 was absent to facilitate reprogramming [35]. On the other hand, regarding the safety concerns of iPS cells, strategies of generating integration-free iPS cells have been developed [55]; however, these reprogramming processes are extremely inefficient and the quality of resulting integration-free iPS cells still needs to be completely characterized [56]. In our study, we identified Zscan4 as a factor, essential for cleavage development of mouse embryos [23], which not only remarkably promotes the efficiency of iPS cell generation, but also significantly improves the quality of iPS cells by stabilizing the genomic and telomere DNA and promoting the telomere elongation at early stage of reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…Although significant progress has been made in terms of improving the efficiency of iPS cell generation through the use of chemical compounds [46,47] and different cell types [48,49], interfering with the epigenetic status of donor cells [50][51][52], or modulating different signal pathways [34,53,54], the quality of iPS cells to date is not significantly improved or even getting worse when the p53 was absent to facilitate reprogramming [35]. On the other hand, regarding the safety concerns of iPS cells, strategies of generating integration-free iPS cells have been developed [55]; however, these reprogramming processes are extremely inefficient and the quality of resulting integration-free iPS cells still needs to be completely characterized [56]. In our study, we identified Zscan4 as a factor, essential for cleavage development of mouse embryos [23], which not only remarkably promotes the efficiency of iPS cell generation, but also significantly improves the quality of iPS cells by stabilizing the genomic and telomere DNA and promoting the telomere elongation at early stage of reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…This bypasses the requirement for early inductive signals from the notochord and neural tube, and provides a method for generating larger quantities of myogenic progenitors, compared with non-genetic techniques. Cells derived from both ESCs and iPSCs have been transplanted into models of MD with some success, demonstrating an overall improvement in functional capacity in terms of muscle force generation [106,[109][110][111]. Myogenic induction of ESCs and iPSCs has also been shown by inducing expression of Met Activating Genetically Improved Chimeric Factor-1 [112].…”
Section: Myogenesis Via Genetic Manipulationmentioning
confidence: 99%
“…Excisable, non-integrating vectors overcome these issues but are typically less efficient. However, use of animal sera remains an issue, as serum is frequently used as a stimulus for terminal myogenic differentiation [106,110,111], and is therefore a limiting factor in clinical application.…”
Section: Myogenesis Via Genetic Manipulationmentioning
confidence: 99%
“…Induced pluripotent stem cells are pluripotent cells with properties similar to embryonic stem cells obtained by reprogramming somatic cells such as fibroblasts [219,220]. In this sense, there were already experiences that demonstrated the possibility of producing myoblasts from induced pluripotent stem cells obtained from mice [221][222][223][224] and humans [225].…”
Section: Experimental Strategies To Avoid Acute Rejection: Autotranspmentioning
confidence: 99%